2014
DOI: 10.3391/bir.2014.3.3.11
|View full text |Cite
|
Sign up to set email alerts
|

Multiple records of aquatic alien and invasive species in diets of native predators in Singapore

Abstract: This is the first systematic assessment conducted on fouling communities to determine the current status of six non-native marine invertebrates that were first recorded in Hong Kong three decades ago. They include the solitary ascidian, Ciona intestinalis; the slipper limpet, Crepidula onyx; the bryozoan, Bugula californica; the Caribbean bivalve, Mytilopsis sallei; the Mediterranean mussel, Mytilus galloprovincialis; and the boring isopod, Sphaeroma walkeri. Field surveys were conducted at 31 locations during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…, Yong et al. ). Snails (i.e., Pomacea canaliculata ) have also been found to alter regime and functioning of aquatic systems (Carlsson et al.…”
Section: Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…, Yong et al. ). Snails (i.e., Pomacea canaliculata ) have also been found to alter regime and functioning of aquatic systems (Carlsson et al.…”
Section: Issuesmentioning
confidence: 99%
“…Aquatic systems have suffered significant losses resulting from invasive plants causing clogging of waterways, and various alien fishes that have out-competed native species and transformed aquatic ecosystems (Yan et al 2001, Yong et al 2014. Snails (i.e., Pomacea canaliculata) have also been found to alter regime and functioning of aquatic systems (Carlsson et al 2004).…”
Section: Invasive Alien Speciesmentioning
confidence: 99%
“…There has been little study on the adaptive behavior of the GHFE. However, Yong (2012) and Yong et al (2014) demonstrated that the species is likely to persist in human-made landscapes such as Singapore, due to its adaptability to novel habitats and prey items.…”
Section: Discussionmentioning
confidence: 99%
“…Though still widely distributed throughout South and Southeast Asia, the GHFE is now only locally common in the latter region, and is declining in other regions such as northeastern India, Nepal, Philippines, and Java, Indonesia (BirdLife International 2017). Although a broad decline is apparent, the species utilizes human-made reservoirs and impoundments in parts of Southeast Asia, including within densely urbanized Singapore (Yong 2012, Yong et al 2014). If the GHFE is able to survive and adapt in human-dominated landscapes (Naoroji 2006, Yong et al 2014, then population declines due to habitat loss and development (BirdLife International 2017) might possibly be mitigated by expansions elsewhere into human-altered landscapes.…”
Section: [Traducción Del Equipo Editorial]mentioning
confidence: 99%
“…Aquatic systems had already suffered great losses and countless non-native fish invasions which have outcompeted indigenous species (Yan et al, 2001). This resulted in the transformation of many aquatic environments (Yong et al, 2014). The introduction percentages of invasive species were increasing rapidly worldwide (Chiron et al, 2009).…”
Section: Introductionmentioning
confidence: 99%